Analysis of Healthcare Associated Infections (HAIs) Surveillance System at Haji Public Hospital of Surabaya - Dwiono Mudjianto; Arief Hargono; Arief Wijaya Rosli (Humanistic Network for Science and Technology (HNST), 2018)
1(CA), 2, 3 1(CA), Indonesia; (Corresponding Author) 2, Indonesia 3 ABSTRACT The incidence of HAIs in Haji Public Hospital of Surabaya in the 1st quarter of 2017 was 0.20% and increased by an average of 56%. Prevention and control measures can be initiated with aseptic setup procedures, comprehensive treatment during tool installation, and possible monitoring of infection by identifying risks through bundle prevention. Bundle prevention is one of the HAIs surveillance that is used to identify and monitor every incident of HAIs in Haji Public Hospital. The purpose of this study was to describe the HAIs surveillance system at Haji Public Hospital. This study used descriptive method of evaluation type. The study was conducted from 7 to 31 August 2017 in the PPI (Infection Prevention and Control) Committee of Haji Public Hospital of Surabaya. The data collected in the form of primary data through interviews and secondary data through documentation study in the form of annual evaluation report or archive of HAIs surveillance data contained in unit PPI Haji Public Hospital. The instruments of data collection used were interview guides and observation sheets in the form of checklist. Data analysis was conducted descriptively on the components and attributes of surveillance. The results obtained from the input components that the competence of surveillance officers are not in accordance with the standards, while the attributes obtained by the results of timeliness, and low data quality. The need to conduct socialization and training of both basic and advanced PPIs and refine technology-based surveillance systems to be more effective and efficient in the implementation of the HAIs infection surveillance system. Keywords: Surveillance, Evaluation, HAIs and Hospital